Allogeneic Stem Cell Transplantation Combined With Transfusion of Mesenchymal Stem Cells in Primary Myelofibrosis: A Multicenter Retrospective Study - Wang, Qingyuan; Xu, Na; Wang, Yu; Zhang, Xi; Liu, Limin; Zhou, Huifen; Wang, Hong; Zhang, Xiang; Tang, Xiaowen; Fu, Chengcheng; Miao, Miao; Wu, Depei (Frontiers in Oncology, 2022)
Background: Allogeneic stem cell transplantation (allo-SCT) remains the only effective curative therapy for primary myelofibrosis. Utilization and efficacy of allo-SCT are limited by lethal complications, including engraftment failure, acute and chronic graft-versus-host disease (GVHD). Several clinical trials have explored use of mesenchymal stem cells (MSCs) in allo-SCT to prevent hematopoietic stem cell (HSC) engraftment failure and control GVHD. Methods: Clinical data of 17 patients with primary myelofibrosis who underwent allo-SCT combined with ex-vivo expanded MSCs transfusion in four centers from February 2011 to December 2018 were retrospectively analyzed. Results: All patients received myeloablative conditioning regimen. The median number of transplanted nucleated cells (NCs) per kilogram body weight was 11.18  108 (range: 2.63-16.75  108), and the median number of CD34+ cells was 4.72  106 (range: 1.32-8.4  106). MSCs were transfused on the day of transplant or on day 7 after transplant. The median MSC infusion number was 6.5  106 (range: 0.011-65  106). None of the patients experienced primary or secondary graft failure in the study. The median time to neutrophil engraftment was 13 days (range: 11-22 days) and the median time to platelet engraftment was 21 days (range: 12-184 days). The median follow-up time was 40.3 months (range: 1.8‐127.8 months). The estimated relapse free survival (RFS) at 5 years was 79.1% and overall survival (OS) at 5 years was 64.7%. Analysis showed that the cumulative incidence of acute GVHD (aGVHD) grade II to IV was 36% (95% CI:8–55%) and that of grade III to IV was 26% (95% CI:0–45%) at day 100. The cumulative incidence of overall chronic GVHD (cGVHD) at 2 years for the entire study population was 63% (95% CI:26–81%). The cumulative incidence of moderate to severe cGVHD at 2 years was 17% (95% CI:0–42%). Seven patients died during the study with 5 patients succumbing from non‐relapse causes and 2 from disease relapse. Conclusion: The findings of the study indicate that allo-SCT combined with MSCs transfusion may represent an effective treatment option for primary myelofibrosis.